2006
DOI: 10.1007/s00213-006-0551-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of alcohol on smoking lapse behavior

Abstract: The primary aim of this project was to examine the role of alcohol use in smoking lapse behavior, as alcohol consumption is a known risk factor for poor smoking cessation outcomes. We have developed a novel human laboratory model to examine two primary aspects of alcohol-mediated tobacco relapse: 1) Does alcohol facilitate the initiation of the first cigarette? 2) Once the first cigarette is initiated, does alcohol facilitate subsequent smoking? Using a within-subject design, 16 daily smokers who were also hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
157
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 77 publications
(95 reference statements)
8
157
1
Order By: Relevance
“…Nicotine withdrawal may lead to increased ethanol consumption in an attempt to reverse withdrawal-associated cognitive deficits, but increased consumption of ethanol also induces cognitive deficits, which could lead to smoking relapse in an attempt to ameliorate ethanol-associated deficits, producing a downward spiral into co-abuse. This hypothesis is supported by findings that nicotine withdrawal is associated with increases in both alcohol craving and consumption (Palfai et al 2000), that the impairments associated with ethanol are reversed by nicotine (Gould and Lommock 2003;Lyon et al 1975), and, finally, that ethanol decreases the ability to limit nicotine consumption (McKee et al 2006). Despite these findings, it is important to remember that the cognitive effects of these drugs comprise only one aspect of co-abuse; alcohol and nicotine also act on the brain's reward system, and interactive effects on this system could increase consumption as well.…”
Section: Discussionmentioning
confidence: 77%
“…Nicotine withdrawal may lead to increased ethanol consumption in an attempt to reverse withdrawal-associated cognitive deficits, but increased consumption of ethanol also induces cognitive deficits, which could lead to smoking relapse in an attempt to ameliorate ethanol-associated deficits, producing a downward spiral into co-abuse. This hypothesis is supported by findings that nicotine withdrawal is associated with increases in both alcohol craving and consumption (Palfai et al 2000), that the impairments associated with ethanol are reversed by nicotine (Gould and Lommock 2003;Lyon et al 1975), and, finally, that ethanol decreases the ability to limit nicotine consumption (McKee et al 2006). Despite these findings, it is important to remember that the cognitive effects of these drugs comprise only one aspect of co-abuse; alcohol and nicotine also act on the brain's reward system, and interactive effects on this system could increase consumption as well.…”
Section: Discussionmentioning
confidence: 77%
“…41 Among middle-aged men with COPD, a 20-year study in three European countries found more than double the risk of death among heavy drinkers compared with light to moderate drinkers. 42 Moreover, drinking has been found to negatively impact smoking cessation, 43 a critical recommendation in the management of COPD. 44 Finally, research on Alzheimer's disease and alcohol consumption has been suggestive of brain protection at lower levels of alcohol consumption but cognitive decline at higher levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the Acheson et al (2006) study, the selfadministration phase commenced while the blood alcohol levels produced by the priming drink were ascending, while our self-administration phase began when the blood alcohol levels were descending. Alcohol-nicotine interactions have been shown to be sensitive to ascending and descending limb effects (King and Epstein 2005;McKee et al 2006;Mitchell et al 1995), and others have demonstrated that medication effects are sensitive to the interval between the priming drink and the self-administration phase (Anton et al 2004). Additional work is needed to delineate how nicotine replacement interacts with temporal effects of the priming drink on inhibiting or promoting further alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, little is known about what effects standard smoking cessation treatments have on alcohol consumption in non-dependent heavy drinking smokers. Alcohol use has been shown to promote smoking relapse across studies using different methodologies (Baer and Lichenstein 1988;McKee et al 2006;Shiffman 1986;Shiffman et al 1996;Zimmerman et al 1990). One way in which smoking cessation medications could promote quitting behavior in this population is by reducing alcohol responses and consumption, thereby attenuating the ability of alcohol to prompt smoking relapse.…”
Section: Introductionmentioning
confidence: 99%